2015
DOI: 10.1089/jmf.2014.3396
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Opuntia ficus-indica Extract Activates AHR-NRF2 Signaling and Upregulates Filaggrin and Loricrin Expression in Human Keratinocytes

Abstract: quinone oxidoreductase 1 (NQO1), which inhibited the generation of reactive oxygen species in keratinocytes challenged with tumor necrosis factor α or benzo[α]pyrene. The antioxidant capacity of OFIE was canceled in NRF2 knockdown keratinocytes. OFIE exerted this NRF2-NQO1 upregulation through activation of the aryl hydrocarbon receptor (AHR). Moreover, the ligation of AHR by OFIE upregulated the expression of epidermal barrier proteins: filaggrin and loricrin. OFIE also prevented TH2 cytokine-mediated downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…Data in the literature shows that most of the phytochemicals upregulate Nrf2 signaling in association with AhR activation [32][33][34]. Besides having an effect on Nrf2, we also noted that S.C. extract has an effect on the AhR pathway.…”
Section: Discussionsupporting
confidence: 65%
“…Data in the literature shows that most of the phytochemicals upregulate Nrf2 signaling in association with AhR activation [32][33][34]. Besides having an effect on Nrf2, we also noted that S.C. extract has an effect on the AhR pathway.…”
Section: Discussionsupporting
confidence: 65%
“…In addition to oxidative stress, recent studies have demonstrated that the AHR system mediates antioxidative and protective signaling in response to certain ligands, such as flavonoids, herbal medicines, and azoles [16,18,19,21,31,32,33]. For example, ligation of AHR by ketoconazole induces the nuclear translocation of AHR without producing ROS.…”
Section: Aryl Hydrocarbon Receptor Regulating Both Oxidative and Amentioning
confidence: 99%
“…Various phytochemicals and herbal extracts exert their antioxidant properties by activating the NRF2 system in an AHR-dependent or AHR-independent manner in human epidermal keratinocytes [18,19,20,21,22]. Certain antioxidant phytochemicals also upregulate the expression of filaggrin (FLG), which plays a pivotal role in maintaining epidermal barrier function [19,20,21,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cynaropicrin results in AhR-dependent NRF2 induction, followed by an increased expression of NQO1, and thereby inhibits ROS production mediated by B[ a ]P or UVB, while CYP1A1 mRNA showed a weak increase. Extracts of Opuntia ficus-indica also lead to an albeit weak but nonetheless significant increase in Nrf2 activity and NQO1 expression AhR-dependently and reduction of B[ a ]P- or TNF α -mediated ROS generation [48]. …”
Section: The Ahr-nrf2 Pathwaymentioning
confidence: 99%